2016
DOI: 10.2174/1875399x01609010104
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Testosterone/Cortisol Ratio Variable in Sports

Abstract: Abstract:This critical review discusses the use of the testosterone/cortisol ratio in the studies of athletic performance and sports physiology. Although in most of the time physical exercise is beneficial to health, it can also be seen as a "stressor" both in men and in women. It is not completely known at what level this "physical stress" ends up its beneficial effects and begins to impair health status. In search for this putative turning point, several markers have been put forward in the last decades. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
0
13
1
4
Order By: Relevance
“…However, the current findings of a systematic review of Cadegiani and Kater (2018) conclude that the COR and T/C ratio are not a good predictor of overtraining syndrome. The most current consensus indicated that the T/C ratio is related to the duration and intensity of training, and this ratio indicates only the tangible physiological strain of training (De Luccia, 2016). In the present study, a significant increase of the T/C ratio was found in those following the ECR and EIR training program, while no changes were observed in other training programs.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…However, the current findings of a systematic review of Cadegiani and Kater (2018) conclude that the COR and T/C ratio are not a good predictor of overtraining syndrome. The most current consensus indicated that the T/C ratio is related to the duration and intensity of training, and this ratio indicates only the tangible physiological strain of training (De Luccia, 2016). In the present study, a significant increase of the T/C ratio was found in those following the ECR and EIR training program, while no changes were observed in other training programs.…”
Section: Discussioncontrasting
confidence: 41%
“…T/C ratio is a variable currently used in the evaluation of the organism response to acute and chronic physical stressors (De Luccia, 2016). Earlier, the relationship between cortisol and testosterone, reflecting anabolic-catabolic balance and the T/C ratio was considered as a marker of overtraining syndrome (Adlercreutz et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ratio between cortisol and testosterone (C/T ratio), the two primary catabolic and anabolic hormones, has been used to determine the degree of systemic catabolic stress in response to exercise (De Luccia, 2016). Here we observed that the C/T ratio dramatically increased following consecutive TKD competitions, but the C/T ratio was sustained at a relatively lower level in participants with simulated intermittent kicking exercise (Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…This hormone is produced by the adrenal cortex and is commonly called the stress hormone because its blood levels increase in response to strong stressors, including psychophysical stimuli (such as sports competitions) [ 12 , 17 , 18 , 19 ] and environmental stimuli (such as exposure to accelerations of >5G) [ 20 ] or sudden hypobaric hypoxia induced in laboratory settings (5000 m) [ 21 ]). As cortisol and testosterone have opposing effects on the rate of endogenous protein metabolism, the idea has emerged to assess the anabolic–catabolic balance as an index of the quotient of molar concentrations (T/C) [ 22 , 23 ]. A significant decrease in the T/C index indicates that the training activity is too high and catabolic processes prevail, which, in extreme cases, may lead to a decrease in skeletal muscle mass.…”
Section: Introductionmentioning
confidence: 99%